APLIKASI PEMBIAYAAN MODAL KERJA MURABAHAH BI AL-WAKALAH PADA BANK MUAMALAT INDONESIA CABANG SUNGKONO SURABAYA - Ahmad Maulidizen; Joni Tamkin bin Borhan (Islam Futura, 2016)
Islamic financing products have been growing rapidly in the banking and financial industry recently. This situation can be seen through the growing number of Islamic banking assets only in several years. Besides, there is also significant growing number of institutions that offer products according to Islamic systems. Murabahah financing products according to Ibn al-Humam is a contract of delivery of goods owned and sold by a person, based on the original price stated in the first contract that increase the profits and declared to the buyer. This study aims to determine the application of working capital financing murabahah bi al-wakalah Bank Muamalat Indonesia Branch Sungkono Surabaya according to Fatwa DSN No. 04 / DSN-MUI / IV / 2000 and Bank Indonesia regulation no. 7/46 / PBI / 2005. In this research the author employed several methods to collect the data including observation, interview and documentation. The author concludes that the implementation of working capital financing murabaha bi al-wakalah at Bank Muamalat Indonesia Branch Sungkono Surabaya is in accordance with the Fatwa DSN No. 04 / DSN-MUI / IV / 2000 and Bank Indonesia regulation no. 7/46 / PBI / 2005.